2022
DOI: 10.33369/consilia.5.1.45-55
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Layanan Bimbingan Kelompok Dengan Teknik Permainan Untuk Meningkatkan Konsentrasi Belajar Siswa

Abstract: Penelitian ini bertujuan untuk mendeskripsikan pengaruh layanan bimbingan kelompok dengan teknik permainan untuk meningkatkan konsentrasi belajar siswa kelas VIII.3 di SMP Negeri 18 Kota Bengkulu. Penelitian ini merupakan penelitian eksperimen dengan desain penelitian one grup pretest dan postest. Teknik sampling yang digunakan adalah purposive sampling, dimana sampel pada penelitian ini adalah 10 orang siswa kelas VIII.3 di SMP Negeri 18 Kota Bengkulu. Hasil penelitian ini menunjukkan adanya peningkatan yang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…The cause of academic stress in the educational system is highly triggered by the inability of students to follow the high demands of the curriculum and the inability of students to follow the rules that have been implemented at school. This is in line with a study carried out by Mardianti & Dharmayana (2020) about the curriculum applied at a school having a mismatch between academic capacity and the academic load received by students, making students feel stressed.…”
Section: Education Systemsupporting
confidence: 87%
“…The cause of academic stress in the educational system is highly triggered by the inability of students to follow the high demands of the curriculum and the inability of students to follow the rules that have been implemented at school. This is in line with a study carried out by Mardianti & Dharmayana (2020) about the curriculum applied at a school having a mismatch between academic capacity and the academic load received by students, making students feel stressed.…”
Section: Education Systemsupporting
confidence: 87%
“…This has been proven in several previous studies, which revealed that the use of group counseling could decrease students' academic stress (Putrikita & Sari, 2020;Koçak & Çelik, 2022). Group counseling could be done using a range of techniques and approaches to address academic stress, such as self-instruction techniques (Mardianti & Dharmayana, 2020), reality-oriented approaches (Fadhlaturrahmah, 2021), stress inoculation (Sriatun et al, 2023), snake ladderbased group counseling (Novaliany, 2022), self-management techniques (Vania et al, 2019), and self-control techniques (Andriati & Hidayati, 2021), among others.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research shows that the use of group counseling can reduce academic stress levels (Putrikita & Sari, 2020;Koçak & Çelik, 2022). In addition, various techniques and approaches in group counseling have been proven effective in reducing academic stress, including using self-instruction techniques (Mardianti & Dharmayana, 2020), reality approach (Fadhlaturrahmah, 2021), stress inoculation in group counseling (Sriatun et al, 2023), snakes and ladders media in group counseling (Novaliany, 2022), self-management techniques in group counseling (Vania et al, 2019), and self-control techniques in group counseling (Andriati & Hidayati, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Salah satunya denegan dengan melakukan diskusi dalam bentuk Fokus Group Discussian (FGD) tentang penyusunan KKM. Focus Group Discussion adalah suau diskusi yang membahsa tentang suatu isu atau masalah yang dilakukan secara sistematis dan terarah (Afriyanti, Handoyo, & Conia, 2022;Fitriani & Azhar, 2019).…”
Section: Pendahuluanunclassified
“…Materi yang didiskusikan adalah berupa permasalahan yang sedang dihadapi yang difokuskan dalam bentuk pertanyaan, tugas-tugas atau pendapat yang harus disampaikan oleh setiap peserta diskusi. Penerapan FGD mampu meningkatkan kemampuan guru-guru menyusun KKM (Afriyanti et al, 2022;Fitriani & Azhar, 2019). Karen melalui pelaksanaan diskusi ini tercipta suasana belajar diantara guru, sehingga pemahaman sikap motivasi dan keterampilan, yang berfungsi untuk memperdalam pengetahuan ataupun cara mengaktualisasikan konsep yang bersifat abstrak mudah dilakukan.…”
Section: Pembahasanunclassified